ASSESSMENT OF THE TAX BURDEN IMPACT ON THE ENTITY'S FINANCIAL RESULTS: MICRO AND MACROECONOMIC ASPECTS - ZAHARCO, Silvia (Journal of Social Sciences)
Taxes are costs for entities that significantly affect the financial results of the economic-financial activity. The level of fiscal burden imposed on taxpayers depends both on the external fiscal environment in which the entity operates and on the characteristics of its financial and economic activities, including its cost structure, sales revenue, income and other indicators. Therefore, to ensure efficient activity, it is necessary to carry out a comprehensive analysis of the impact of fiscal burden on the entity's financial results. The purpose of this research is to assess the level of fiscal burden and determine the degree of influence on some indicators that characterize the economic-financial activity of the entity. The study is based on the methods of assessing the fiscal burden applied in international practice at both the micro and macroeconomic levels. The study reveals that in order to determine the fiscal burden, especially at the microeconomic level, there is a need to combine several indicators, in accordance with the conceptual approach to the analysis of the tax system. Therefore, increasing the entity's financial results does not only involve reducing taxes, but creating an efficient system for managing and optimizing the entire taxable system.